The Five Stars of Neli Aparecida de Mello-Théry - Sampaio, Mateus de Almeida Prado (Management & Public Policies Journal, 2023)
This text aims to critically analyze the work of Neli Aparecida de Mello-Théry and at the same time pay him a simple tribute. The five scientific works chosen by the author to compose the hall of the most significant publications of her career are evaluated with greater attention, almost in a review format. These were marked with a prominent star on her CNPq/Lattes online curriculum. Initially a professional retrospective of the author is drawn for the following analysis of five highlighted works: L'État brésilien et l'environnement en Amazonie: évolutions, contradictions et conflits (2003); Políticas territoriais na Amazônia (2006); Atlas do trabalho escravo no Brasil (2012); Politiques environnementales brésiliennes: intentions et réalités (2017) e Disparidades e dinâmicas do território (2018). As common characteristics to all of these publications there are the environmental issue and the role of public policies in the delineation of the directions given to the territorial development of the country, especially in the Amazon: deep, comprehensive, pressing and necessary themes.